Identifying and Developing the Main Agricultural Commodities Around Kerinci Seblat National Park, Lebong Regency - Romdhon, Muhamad Mustopa; Nola Windirah; Hariz Eko Wibowo (Jurnal AGRISEP, 2026)
This research investigates the superior agricultural commodities in villages surrounding the Kerinci Seblat National Park (KSNP), Lebong Regency, aiming to identify the main agricultural commodities and elucidate the enabling conditions for their sustainable development. This study contributes to the broader goal of achieving harmony between human prosperity and environmental sustainability in the KSNP. A mixed-methods approach was employed, using a quantitative Location Quotient (LQ) analysis of production data from 21 villages to identify main commodities. The total number of respondents was 105 farmers and four expert respondents (the Department of Agriculture, Head of a Farmer Group, Businessman, and an academic). This study used both primary and secondary data sources. Primary data were obtained through a survey using structured instruments to obtain information from farmers. The study concludes that the villages around the KSNP have a variety of main agricultural commodities. Each village has advantages in commodity diversification, a high degree of specialization, and an integrated Cultivation Model. The sustainable development of the main agricultural commodities in villages around the KSNP faces several opportunities and challenges. The main opportunities are downstream product development, access to premium and export markets, and agro-tourism. The main challenges faced by almost all villages are similar, rooted in their geographic location are limited land and regulations, infrastructure and market access, and price management.